Development of a web-based Multimedia Learning Management System (MLMS) in High School physics learning - Taufik Solihudin Jh; Suwardi Annas; Syukur Saud (Universal Teaching and Learning Journal, 2025)
Purpose: To develop and evaluate a web-based Multimedia Learning Management System (MLMS) for high school physics integrating text, images, video, animation, and simulations to address post-pandemic learning challenges and improve outcomes in static and dynamic electricity. Research Methodology: Research and Development using the ADDIE model. Needs analysis involved questionnaires to teachers (n=30) and students (n=107). The MLMS was designed and developed with multimedia and PhET-based virtual labs, then validated by material and media experts, followed by small-group (n=17) and field trials with teachers and students. Data were analyzed using 4-point Likert means; learning-outcome instruments were prepared with validity/reliability procedures, and effectiveness was examined with a pretest–posttest (N-Gain) design. Results: Needs analysis showed strong demand for accessible, multimedia physics resources (teachers 100% supportive; students 98% agree on development). Material validation achieved a very good category (~90%+), media validation very good (?83.75%). Small-group practicality averaged 86.32% (very good); teacher field tests averaged 84.82% (very good); student responses averaged 79.98% (very good). Implementation indicates improved learning outcomes in static and dynamic electricity. Conclusion: The web-based MLMS is valid and practical for classroom use, enhances engagement through interactive multimedia and simulations, and supports better monitoring of student progress. Limitations: Trials were limited to selected schools and physics topics; no randomized control groups; effectiveness depends on stable internet access. Contribution: Provides a validated MLMS prototype that operationalizes ADDIE for physics education, integrates interactive multimedia and virtual labs with progress tracking, and offers instruments and practical guidance for school-level deployment.